Study guides

☆☆

Q: The sum of 3 times a and b?

Write your answer...

Submit

Still have questions?

Related questions

It is the same as: 3*(a+b) or simply 3(a+b)

3*(a + b) or 3a + 3b

3(a + b) + a = 3a + 3b + a = 4a + 3b

3(b5)

3(a+b)+a

The algebraic expression is 3(b+5).

(3+b)

The sum of xy times 3 is equal to 3(xy).

the sum of 3 times m and n

To multiply a sum by a number,multiply each addend of the sum by the number outside the parentheses.For any numbers a, b, and c, a(b+c) = ab + ac and a(b-c) = ab - ac.Example: 2(5-3)= (2 times* 5) - (2 times* 3). Times*_multiply

5a plus 2b

1.Start 2. Input a,b,c 3. Sum = a+b+c 4. Average = sum/3 5. Output - Sum,Average 6. Stop

a^3 + b^3 = (a + b)(a^2 - ab + b^2) a^3 - b^3 = (a - b)(a^2 + ab + b^2)

300

141

3 times a times a times b

if the sum of three is six then it would be 30 right?? i think depends on wat sum of 3 is

The algebraic expression for the sum of 11 times 5 and three is 11s+3

//sum and product of 3 nos #include #include void main() { int a,b,c; printf("enter the 3 nos"); scanf("%d%d%d",&a,&b,&c); printf("sum of 3 nos",a+b+c); printf("product of 3 nos",a*b*c); getch(); }

a + b = 14, so a = 14 - b; 6a - 3b = 3;substitute: 6(14 - b) - 3b = 3, ie 84 - 6b - 3b = 3, ie 81 = 9b so b = 9 and a = 5

the answer is 9

5x + 6

5(a+b)-7

It is: 5*(b+2) which is the same as 5b+10

a + b = 21 so a = 21 - b; 3a = 4b so 3(21 - b) = 4b ie 63 - 3b = 4b so 7b = 63 making b = 9 and a = 12

People also asked